Validation of a tele-robotic ultrasound system for abdomen and thyroid gland explorations: a comparison with standard ultrasound - Antolin, Andreu; Roson, Nuria; Planes, Marina; Castillo, Mar; Alberti, Anna; Escobar, Manuel (The Ultrasound Journal, 2025)
Background: Tele-robotic ultrasound (US) is a novel technique that might help overcome the current shortage of radiologists and poor access to radiologists and/or sonographers in remote or rural areas. Despite the promising results of this technology in the past two decades, there is still insufficient data about its advantages and limits, as well as the implementation in routine clinical practice and the learning curve for the user. The purpose of this prospective cohort-based study is to evaluate the performance of a 5G-based tele-robotic US system for abdominal and thyroid gland assessment in a cohort of healthy volunteers and outpatients, as well as assessing the learning curve and patient satisfaction. Results: 64 participants (23 male, 41 female) were consecutively included during the recruitment period, for a total of 51 abdominal and 37 thyroid gland US studies. The mean age was 45.23 ± 18.90 years old, and the body mass index of the abdominal cohort was 22.97 ± 2.95 kg/m2. The learning curve estimated a minimum of 20 patients for abdominal tele-robotic US training, being almost non-existent in the thyroid gland cohort. All the variables showed no-statistical differences between standard US and tele-robotic US in the abdominal post-trained cohort except the visualization of the left kidney short axis and its interpolar length. Thyroid gland variables showed no statistical differences. The mean time of exploration for the tele-robotic US for abdomen and thyroid gland examinations were 18.33 ± 6.26 min and 4.64 ± 0.97 min respectively. Most participants (> 70%) felt comfortable and safe while being examined by the tele-robotic US. Conclusion: Tele-robotic US achieves equal performance in comparison with the standard US when evaluating abdominal structures in this cohort of patients, as well as a relatively fast learning curve and good patient satisfaction. The performance when assessing the thyroid gland is almost identical to the standard US, which makes it a strong first candidate for a future clinical implementation.